Social vulnerability factors in immigrant Nicaraguan impoverished population in Costa Rica, 2019 - Hernandez Murillo, Jason (2022)
Introduction: Nicaraguan immigrant population is the most representative in Costa Rica, and when a comparison is established, it is observed that there are higher levels of poverty in migrant households compared to those of the native population, in such a way that the purpose of this investigation is to know what factors produce vulnerability in these dwellings. Methodology: This is a quantitative approach study using the ENAHO 2019 database used to measure poverty, first, in a descriptive scope through characterizations of contingencies between the population of Nicaraguan and autochthonous origin and later, in an explanatory one using regression logistic models, to find significance and reinforce the findings. Results: There are factors that put the impoverished Nicaraguan immigrant population in serious situations of vulnerability, in which factors such as labor exploitation coupled with the lack of access to health insurance were seen. In other words, these would be the main factors of social vulnerability. Conclusions: It was evidenced that the Nicaraguan immigrant population has shortcomings in better working conditions and access to health insurance, in addition it is subjected to labor marginality, in fact this function as vulnerability factors, and that they serve to obtain and exploitation of cheap labor in the capitalist dynamics of people in households headed by Nicaraguan immigrants.